2020
DOI: 10.21203/rs.3.rs-26301/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychosocial Support Interventions for Improved Adherence and Retention in ART care for Young People Living with HIV (10-24 years): A Scoping Review

Abstract: Background: Mental health disorders such as high levels of anxiety, isolation, depression and suicide ideation reported among young people living with HIV (10-24 years; YPLWH) contribute significantly to poor medication adherence and retention in care. While there is evidence supporting the role of psychosocial support interventions in promoting adherence and retention in antiretroviral treatment (ART) among adults living with HIV, there is little evidence on the role of psychosocial support on medication adhe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…During their period of severe distress after obtaining results, family members were often there to offer support. This is similar to findings from other studies; for instance, Okonji et al ( 2020 ) who believe that social support is an important factor for health maintenance. Kumala et al ( 2022 ) established that family social support has a positive influence on people living with HIV as they face stress related to health-disease process, contributing towards the treatment against HIV and dealing with aspects related to the fear of death.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…During their period of severe distress after obtaining results, family members were often there to offer support. This is similar to findings from other studies; for instance, Okonji et al ( 2020 ) who believe that social support is an important factor for health maintenance. Kumala et al ( 2022 ) established that family social support has a positive influence on people living with HIV as they face stress related to health-disease process, contributing towards the treatment against HIV and dealing with aspects related to the fear of death.…”
Section: Discussionsupporting
confidence: 92%
“…Focused on education and counselling, psychosocial support can be associated with the following positive outcomes: increased rates of disclosure, greater treatment adherence, reduction in unprotected sex as well as HIV transmission (Mashaphu, Burns, Wyatt, & Vawda, 2018 ). In addition, utilisation of psychosocial interventions such as counselling, cognitive behavioural therapy, and peer support have proved to be effective in improving the mental health and overall well-being of people living with HIV (Okonji, Mukumbang, Orth, Vickerman-Delport, & Van Wyk, 2020 ). Such psychosocial support interventions are specifically meant to promote HIV disclosure and communication, address feelings of emotional-related distress, and challenges associated with HIV serodiscordancy (Schotanus-Dijkstra et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychosocial support (PSS) interventions can help ALHIV overcome barriers to adherence and retention in ART care thereby improving immunological health outcomes [ 24 ]. However, there are currently limited understanding on how psychosocial support interventions improve adolescents´ ART adherence, retention in care and immunological health outcomes [ 25 ]. A recent scoping review showed that individual and group counselling including family-centred group counselling and the use of adolescent treatment supporters were commonly used intervention to improve ART adherence, linkage to care and/or retention in care among adolescents living with HIV [ 25 ].…”
Section: Commentarymentioning
confidence: 99%
“…However, there are currently limited understanding on how psychosocial support interventions improve adolescents´ ART adherence, retention in care and immunological health outcomes [ 25 ]. A recent scoping review showed that individual and group counselling including family-centred group counselling and the use of adolescent treatment supporters were commonly used intervention to improve ART adherence, linkage to care and/or retention in care among adolescents living with HIV [ 25 ]. Using the biopsychosocial model [ 26 ], we formulated hypotheses to explain how the components of the RTC ALHIV intervention is designed to improve adherence to ART and retain ALHIV in ART to improve health outcomes.…”
Section: Commentarymentioning
confidence: 99%